Leptospira strains isolated from cattle in the Amazon region, Brazil, evidence of a variety of species and serogroups with a high frequency of the Sejroe serogroup. (February 2021) - Guedes, Israel Barbosa; Souza, Gisele Oliveira de; Rocha, Katarine de Souza; Cavalini, Matheus Burilli; Damasceno Neto, Manoel Soares; Castro, Juliana Fernandes de Paula; Souza Filho, Antônio Francisco de; Negrão, Manoel Pierre; Cortez, Adriana; Moraes, Carla Cristina Guimarães de; Heinemann, Marcos Bryan
Highlights: 52 Leptospira isolates recovered from cattle raised in the Brazilian Amazon were characterized. The isolates belonged to different species and serogroups. Strains from the Sejroe serogroup were isolated for the first time in Brazilian Amazon. Some genotypes may represent new strains not yet characterized. Abstract: In Brazil, there have been few leptospires isolated from cattle, especially in the Amazon, implying that the epidemiology of the disease in this region is still largely unclear. In a previous study, 52 Leptospira isolates were obtained from urine of cattle raised in the Brazilian Amazon and, to achieve a greater understanding of Leptospira infection in cattle of this region, the present study aimed to serologically and molecularly characterizes all these isolates. The laboratory assays used were the microscopic agglutination test (MAT) adopting a panel of polyclonal antisera against Leptospira spp. for serogrouping the isolates, DNA sequencing ( secY ) and multiple locus variable number tandem repeat analysis (MLVA). The isolates belonged to five species: 20/52 were identified as L. borgpetersenii (38.5 %); 18/52 as L. kirschneri (34.6 %); 9/52 as L. santarosai (17.3 %); 3/52 as L. noguchii (5.8 %) and 2/52 as L. interrogans (3.8 %). With serogrouping, nine different serogroups were detected, with a high frequency of the Sejroe serogroup. MLVA showed that all L. borgpetersenii isolates had a profile compatible with serovar Hardjo; moreover, the other isolates demonstrated a diversity of patterns, and some of them may represent strains not yet characterized. In the Brazilian Amazon, the leptospires circulating in cattle revealed the unique aspects of infections in this area which, in addition to a variety of strains, were characterized by a high frequency of the Sejroe serogroup, highlighting the serovar Hardjo, which has not been reported in other regions of Brazil.